PENGELOLAAN MANAJEMEN RISIKO BENCANA ALAM DI INDONESIA - Paidi, Paidi (MAJALAH ILMIAH WIDYA, 2012)
The natural disaster such as earthquake, tsunami, volcano eruption, hurricane, flood and landslide may occur to anyone, whenever,and wherever. According to the various sources, in Indonesia 87% are the natural disaster prone regions, or of 440 Urban/Regencyterritories, 383 out of them are natural disaster prone regions. The objective of this paper is to assist the socialization the understandingof the community in Indonesia on natural disaster is very low. The data or information is obtained from the bibliography of varioussources. What should be taken into account are the focus on the preparedness, impact mitigation, emergency response, rehabilitationand recovery as well a reconstruction which can be conducted to minimize the impact, and the affected area will be expectedlyrecoverable as usual, and even improved mentally, economically, infrastructural and in other social life.